Pendampingan Digitalisasi Koperasi Pada Koperasi Karyawan Sejahtera Universitas PGRI Yogyakarta - Rima Elya Dasuki; Lutfhi Nurul; Mishel Febriani (E-Coops-Day, 2023)
Effective use of technology is urgently needed in the era of the industrial revolution 5.0, includingcooperatives as one of the aspects that support the success of cooperatives. The success ofcooperatives will play a very important role in the sustainability of cooperative development whereincreasing the welfare of members is a goal that must be achieved. Member welfare can beachieved if the cooperative can manage its activities optimally. The field practice activities ofIndonesian Cooperative University students carried out at the PGRI Jogjakarta UniversityCooperative in February 2013, one of the activities was assisting in the digitalization ofcooperatives which included computerization in the secretarial and operational fields, especiallythe financial aspects. This assistance was a good collaboration between the IndonesianCooperative University and cooperative management who will use the results of student work sothat one of the objectives of the field practice is to participate in improving the competence ofadministrators to achieve.